A study of COVID-19 infection, severity and associated factors among the patients admitted at a tertiary care center in southern Rajasthan - Hirani, Jitendra; Dixit, Mukul; Verma, Anjana; Mathur, Medha (International Journal Of Community Medicine And Public Health, 2023)
Background: Since December 2019, there has been various outbreaks of corona virus disease 2019 (COVID-19) disease. Whole world is combating this virus, but its reported clinical characteristics as well as outcomes vary greatly amongst studies. This study was conducted to study the clinical features, laboratory findings, comorbidities and severity of the disease among the patients admitted in tertiary care centre in Rajasthan. Methods: It was a hospital-based cross-sectional study conducted from 1st January 2021 to 30th June 2022 in a tertiary care hospital in Udaipur, Rajasthan. All the patients diagnosed with the help of reverse transcription polymerase chain reaction (RTPCR) for COVID-19, during the study period were included in the study. After taking consent, pre designed questionnaire was used to collect the personal, demographic and clinical information. Radiological, laboratory and mortality data were collected from hospital record. Results: A total of 400 patients were included in the study. Mean age of the patients was 46.83±17.09 years. Fever (88%) and cough (80%) were the most common symptoms followed by breathlessness (65.8%). About 31.8% (127) patients were found to have severe covid. Severity was found to be significantly associated with increasing age, urban area, breathlessness, co morbidities and D dimer, CRP and IL-6 levels (p value <0.05). Conclusions: India being a diverse country with a range of sociodemographic characteristics existing within the population, needs a robust approach to control the COVID 19 pandemic. This study presents the factors associated with severe disease and can help to formulate preventive and control strategies.